The European Union’s democratic deficit and options for EU democracy in the 21st century - Lee, Dexter (2015)
The European Union (EU) is widely acknowledged as a successful example of economic and political integration of nation states today – a slate of democratic institutions such as the European Parliament have also been developed and European citizens now possess extensive political and civil rights by virtue of the introduction of European citizenship. Nevertheless, the EU is said to suffer from a so called “democratic deficit” even as it seeks deeper and closer integration. Decades of institutional design and elite closed-door decisions has taken its toll on the inclusion and integration of European citizens in social and political life, with widening socio-economic inequalities and the resurgence of extreme-right parties during in the wake of the debt crisis in the Eurozone. This paper attempts to evaluate the democratic development of the EU through the use of a process-oriented approach, and concludes at the end with discussions on the various options that the EU and its citizens can take to reform democratic processes and institutions in Europe.